A COMMENTARY UPON GADAMER’S INTERPRETATION OF HEGEL - CRIŞAN, Anton (Studia Universitatis Babeș-Bolyai Philosophia, 2015)
A Commentary upon Gadamer’s Interpretation of Hegel. In light of a renewed scholarly undertaking of the Hegel‒Gadamer connection, the purpose of the present paper is to carry further this much needed re-approach of the issue by stressing yet another one of its aspects. I am referring to the scholarly insights that Gadamer himself provides us with in his interpretation of Hegel. Since many of Gadamer’s essays on Hegel are actually studies originally meant as contributions to major journals dealing with Hegel’s work, my claim is that we can retrieve from them answers to many ongoing debates in the Hegel scholarship. I will insist on only one of these issues, namely Gadamer’s account of Hegel’s relation to metaphysics.